족근동 증후군으로 오인된 Accessory Anterolateral Talar Facet에 의한 거종관절 충돌 - 박재우; 박철현; Park, Jae Woo; Park, Chul Hyun (대한족부족관절학회지, 2018)
Purpose: To evaluate the clinical and radiographic results of surgical treatment for patients with sinus tarsi pain due to accessory talar facet impingement. Materials and Methods: Between July 2013 and July 2015, nine patients who underwent surgery for the accessory talar facet impingement were reviewed. The mean follow-up period was 18.6 months (12~36 months), and the mean age was 33.1 years (19~60 years). Previous trauma history, duration of symptom, and types of surgery were analyzed. The clinical results were evaluated using the American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score and visual analogue scale (VAS). Radiographic results were assessed using Meary's angle, calcaneal pitch angle, heel alignment angle, and heel alignment ratio. Results: All patients had evident trauma history prior to the initial symptom. The mean duration of symptoms was 25.6 months (6~120 months). Four patients received only accessory anterolateral talar facet (AALTF) excision, and four patients received medial sliding calcaneal osteotomy (MSCO). One patient underwent both AALTF excision and MSCO. The AOFAS ankle-hindfoot score was significantly improved from 73 (62~77) preoperatively to 93 (67~100) postoperatively. The VAS score was decreased from 6 (5~7) preoperatively to 1 (0~5) postoperatively. The Meary's angle and calcaneal pitch angle showed no significant difference after surgery. The heel alignment angle and ratio increased from $-3.6^{°}$ ($-10^{°}{\sim}5^{°}$) and 0.22 (-0.15~0.6) preoperatively to $2.8^{°}$ ($1^{°}{\sim}5^{°}$) and 0.42 (0.3~0.6) postoperatively, respectively. Conclusion: If there is persistent sinus tarsi pain in patients with hindfoot valgus, accessory talar facet impingement caused by AALTF could be considered as a cause of chronic sinus tarsi pain.